Case report: Rapid resolution of grade IV ICANS after first line intrathecal chemotherapy with methotrexate, cytarabine and dexamethasone - Katsin, Mikalai; Shman, Tatsiana; Migas, Alexandr; Lutskovich, Dzmitry; Serada, Yuliya; Khalankova, Yauheniya; Kostina, Yuliya; Dubovik, Simon (Frontiers in Immunology, 2024)
Corticosteroid therapy is the mainstay of immune effector cell-associated neurotoxicity syndrome (ICANS) management, although its use has been associated with worse overall survival (OS) and progression-free survival (PFS) after chimeric antigen receptor T-cell (CAR-T cell) therapy. Many options are being investigated for prophylaxis and management.Accumulating evidence supports the use of intrathecal (IT) chemotherapy for the management of high-grade ICANS. Here, we describe a case of a patient with stage IV Primary mediastinal Bcell lymphoma (PMBCL) successfully treated with IT methotrexate, cytarabine, and dexamethasone as first-line therapy for CD19 CAR-T cell-associated grade IV ICANS. The stable and rapid resolution of ICANS to grade 0 allowed us to discontinue systemic corticosteroid use, avoiding CAR-T cells ablation and ensuring preservation of CAR-T cell function. The described patient achieved a complete radiologic and clinical response to CD19 CAR-T cell therapy and remains disease-free after 9 months. This case demonstrates a promising example of how IT chemotherapy could be used as first-line treatment for the management of high-grade ICANS.Chimeric antigen receptor T-cell (CAR-T cell) therapy has recently emerged as a novel treatment modality for the management of B-cell acute lymphoblastic leukemia, non-Hodgkin lymphoma, and multiple myeloma, with high response rates and a potential for cure. To date, the Food and Drug Administration has approved six CAR-T cell products for different indications, and numerous CAR-T cell trials are being widely carried out. Despite great clinical success, complications such as cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS) can be fatal and can pose obstacles in the clinical application of CAR-T cells. Anti-IL-6 receptor antibody (Tocilizumab) and corticosteroid therapy are the mainstream management strategies for CRS and ICANS, respectively (1). It was recently reported that a high cumulative corticosteroid dose, especially in high-grade ICANS, is